Asymmetric α-Cyanation of β-Keto Esters Catalyzed by Chiral Tin Alkoxides - Yanagisawa, Akira; Hinata, Yuki; Midorikawa, Koji; Watanabe, Takamichi (Synlett, 2023)
A catalytic enantioselective α-cyanation reaction of β-keto esters with p-toluenesulfonyl cyanide (TsCN) as a cyanating reagent was achieved using an (R)-BINOL-derived chiral tin dibromide possessing 4-tert-butylphenyl groups at the 3- and 3′-positions as a chiral precatalyst in the presence of sodium ethoxide in ethanol. Optically active α-cyano-β-keto esters having a chiral quaternary carbon were obtained in good to high yields under the influence of the chiral tin diethoxide generated in situ.
Keywords: asymmetric catalysis; cyanating reagent; cyanation; keto esters; tin catalysis